ANALYSIS OF THE END-USER RESPONSES TOWARDS BIOPHILIC DESIGN IMPLEMENTATION IN MALAYSIAN PRIVATE HOSPITALS - Zakaria, Nurul Zalifah; Ahmad, Suriati; Amir, Atikah Fukaihah (PLANNING MALAYSIA, 2024)
Hospitals are the central place to get treatment, especially during the COVID-19 pandemic that badly hit the world. Significantly, hospitals need a healing environment promoting health and well-being. One initiative is integrating biophilic design as done by international hospital building design to maximise the human-nature relationship in a hospital environment. Hence, the positive impacts of green hospitals enable biophilic design to be applied in Malaysia. Therefore, this study aims to identify the successful implementation of biophilic design for space planning in Malaysian green hospitals. A questionnaire survey method with two hundred respondents was conducted, and the questionnaire survey data were analysed using Statistical Package for Social Science (SPSS). From the analysis of the end-user responses, ten biophilic design elements have been discovered to help improve the health and well-being of the hospital end users, including patients, staff and visitors. These research findings further demonstrate the potential of biophilic design to be implemented in Malaysian private hospital designs to enhance the healing environment supporting the medical health care system.